AMBIDEXTERITY CAPABILITIES AND HUMAN CAPITAL IN INDONESIAN TOURISM MSMEs PERFORMANCE - Tarigan, Imanuel; Harsono, Subambang; Subiantoro, Nur; Sitompul, Pandapotan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Indonesian tourism MSMEs have a low level of resilience, making them unprepared for crises like the COVID-19 pandemic. This is due to a lack of resources for organizational adaptability. Researchers are exploring the role of organizational resilience and strategic renewal in improving the performance of these MSMEs. Structural equation modeling (SEM) analysis shows a positive relationship between ambidexterity capability and human capital on strategic renewal, and strategic renewal positively impacts performance. However, organizational resilience has little impact on strategic renewal. Factors such as limited resources and unpreparedness for economic crisis conditions impede the resilience of these MSMEs.